Educational Outreach: Stop Bullying, Stop Seniority in Schools - Masita, Ella; Widyastuti, Widyastuti; Dama, Melati; Sumardi , Sumardi; Munizu , Musran (Journal Of Human And Education (JAHE), 2024)
Bullying behavior carried out by seniors towards juniors in the educational environment is still often found in various schools and is still a hot topic that is often discussed today. Cases of violence perpetrated by seniors against juniors have attracted a lot of attention because cases of violence used by seniors against juniors still exist today. Therefore, the aim of this community service is to see what factors are behind violent behavior in seniority in the educational environment and to provide education to students that the acts of bullying carried out are deviant acts and can be traumatic for the victims of bullying. In obtaining the data used were observation and literature review. This service activity is an effort to educate bullying behavior and seniority at Junior High School Number 17 Jambi. This effort was motivated by the lack of knowledge about bullying. As a form of the author's thinking, several efforts and breakthroughs are offered, namely; 1.) Children are given reinforcement regarding the ability to detect early the possibility of bullying, 2.) Families need to instill religious values ​​and teach love between each other 3.) Schools can design and design programs to prevent bullying behavior, 4.) Prevention efforts community by building groups that care about child protection starting from the village or sub-district level to the district or city and provincial levels.